Podmiotowość ponowoczesna: wieloznaczność tożsamości czy tożsamość wieloznaczności. Propozycja Zygmunta Baumana - Richert, Sebastian (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2010)
In my research I will try to analyse Zugmunt Bauman reflection about human subject. This author applies rather identity than human subject, but I think we may admit Apple subjectivity instead of identity. Bauman's concept of model personality like a pilgrim on one hand and a stroller, vagabond and player on the other hand, link these categories of human subject. Identity of human subject is continually made "liquid" and has constant potency to change. In consequence, identity is an infinite aimless process because its main determinant – certainty of future connected with values (truth or worth) – are to distort. Does identity in postmodern age is just a wish, which is not realized? Does identity prop on conflict in human existence and never is constant? I will try to go through that and another question and possible answers within Bauman philosophy. In the contemporary debate we see a strong tendency to make a distance to Maxim description. The main problems like truth, subject or knowledge are used in its context. This intellectual climate depends on the basic modernist guidelines. The Cartesian model of cognition especially the strong possibility of cognition is challenged. Lyotard, Foucault, Rorty or Bauman support that tendency.